A Fast Solution to the Conjugacy Problem in the Four-Strand Braid Group - Calvez, M (Walter de Gruyter GmbH, 2014)
We present an algorithm for solving the conjugacy search problem in the fourstrand braid group. The computational complexity is cubic with respect to the braid length. © de Gruyter 2014.